Teilhard de Chardin and the Theology of Creation Today. Some Structural Elements and Current Concepts - Florio, Lucio (Razón y fe, 2024)
The work of Pierre Teilhard de Chardin knows a second wave of interest, after that experienced after the publication of his writings after his death. Several of his themes have been taken up by thinkers and theologians. In the light of this reception, it is interesting to detect the Teilhardian structures and concepts that can help to renew the systematic treatise on the Creator God and the catechetical and pastoral expositions related to the divine creation. The scientific-philosophical structure expressed in concepts such as cosmogenesis, biogenesis, noogenesis, Christogenesis, omega point and others is useful to rethink the theology of creation in a time of predominance of the sciences.